2019
DOI: 10.1111/jocn.14878
|View full text |Cite
|
Sign up to set email alerts
|

How to use visual methods to promote health among adolescents: A qualitative study of school nursing

Abstract: Aims and objectives Public health nurses attended a 3‐day course to learn the use of visual methods in health dialogue with adolescents. The aim of this study was to explore how to use visual methods to promote health among adolescents in a school nursing context. Background Photovoice is a visualising technique that enables adolescents to participate in health promotion projects in a school setting. Photovoice also enhances work of public health nurses and other health professionals. Design This was a qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…To some degree, most studies aimed to use photovoice to teach participants about factors impacting health at the individual, community, and environmental levels, with topics such as health care costs (Gwon & Thongpriwan, 2019), HIV (Leyva‐Moral et al, 2021), global health and cultural diversity (Michael et al, 2012), intimate partner violence (Solano‐Ruiz et al, 2021), mental illness (Tippin & Maranzan, 2022), and rural nursing (Yonge et al, 2013). Conversely, one study used photovoice to describe the experience of nurses learning a new clinical training system in the hospital (Horii et al, 2021) and another examined how a photovoice intervention impacted the relationship between school nurses and adolescents (Laholt et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To some degree, most studies aimed to use photovoice to teach participants about factors impacting health at the individual, community, and environmental levels, with topics such as health care costs (Gwon & Thongpriwan, 2019), HIV (Leyva‐Moral et al, 2021), global health and cultural diversity (Michael et al, 2012), intimate partner violence (Solano‐Ruiz et al, 2021), mental illness (Tippin & Maranzan, 2022), and rural nursing (Yonge et al, 2013). Conversely, one study used photovoice to describe the experience of nurses learning a new clinical training system in the hospital (Horii et al, 2021) and another examined how a photovoice intervention impacted the relationship between school nurses and adolescents (Laholt et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Despite limited studies describing data dissemination, many articles included either a group discussion or a critical dialogue component, which is integral to the photovoice process (Wang & Burris, 1997). Even so, six studies included neither a discussion nor a dissemination component (Laholt et al, 2019; Leipert & Anderson, 2012; Michael et al, 2012; Oosterbroek, 2019; Stupans et al, 2019; Yonge et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants received material explanations from the trainer presentations with additional visual images. The use of image visualization for health education in adult groups could trigger participants to play an active role in discussions and submit topics to ask further questions to the trainers [23]. One of the methods in training was an interactive discussion using case studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their review paper on the role of pictures in improving health communication, Houts et al (2006) concluded that visual information can remarkably increase attention to, comprehension of and recall of health information, particularly when the visuals are closely related to the text information. In another study, Laholt et al (2019) conducted a qualitative study aiming to promote health among adolescents through the use of visual methods, and they found that the use of images promotes health communication among adolescents.…”
Section: Related Studiesmentioning
confidence: 99%